Effect of heat processing on selected grain amaranth physicochemical properties - Muyonga, John H.; Andabati, Brian; Ssepuuya, Geoffrey (Food science & nutrition, 2014)
Grain amaranth is a pseudocereal with unique agricultural, nutritional, and functional properties. This study was undertaken to determine the effect of different heat-processing methods on physicochemical and nutraceutical properties in two main grain amaranth species, of Amaranthus hypochondriacus L. and Amaranthus cruentus L. Grains were prepared by roasting and popping, milled and analyzed for changes in in vitro protein digestibility, gruel viscosity, pasting characteristics, antioxidant activity, flavonoids, and total phenolics. In vitro protein digestibility was determined using the pepsin-pancreatin enzyme system. Viscosity and pasting characteristics of samples were determined using a Brookfield Viscometer and a Rapid Visco Analyzer, respectively. The grain methanol extracts were analysed for phenolics using spectrophotometry while antioxidant activity was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Heat treatment led to a reduction in protein digestibility, the effect being higher in popped than in roasted samples. Viscosities for roasted grain amaranth gruels were significantly higher than those obtained from raw and popped grain amaranth gruels. The results for pasting properties were consistent with the results for viscosity. In both A. hypochondriacus L. and A. cruentus L., the order of the viscosity values was roasted>raw>popped. The viscosities were also generally lower for A. cruentus L. compared to A. hypochondriacus L. Raw samples for both A. hypochondriacus L. and A. cruentus L. did not significantly differ in total phenolic content (TPC), total flavonoid content (TFC), and total antioxidant activity values. Thermal processing led to an increase in TFC and antioxidant activity. However, TPC of heat-processed samples remained unchanged. From the results, it can be concluded that heat treatment enhances antioxidant activity of grain amaranth and causes rheological changes dependent on the nature of heat treatment
Keywords: Antioxidant activity; flavonoids; grain amaranth; pasting properties; phenolics; protein digestibility